An integrated model of motivational factors affecting employees with disability -Finding from Indian Public Sector Undertaking, survey - et al., Jigyasu Kumar (International Journal of Advanced Science and Technology, 2019)
The imperative need for enhancing motivation for employees with Disabilities is a major concern for the organizations. We have created and assessed motivational factor affecting employee with disability i.e Motivational Factor Inventory for employees with disabilities (MFIED) at workplace The MFIED comprises of 48 items compiled together in seven motivational dimensions. These dimensions are as follows; 1.Dignity at workplace 2.Interpersonal relation 3.Personal Development    4. Working conditions 5. Task/assignment at workplace 6.Salary, compensation and benefits       7. Empowerment .Result of this study showed that MFIED as a valid instrument and all the identified 48 items were admissible for employees’ with disability. Job Security, Timely promotion and work life balance have been identified as the most important motivators affecting employees with disabilities, working at Rashtriya Ispat Nigam Limited,  A Central Public Sector Undertaking under the administrative control  of Ministry of Steel, Govt. of India. Factors related to Salary, compensation and Benefits are the least important motivators. Motivation cannot be obtained everywhere and always with the same recipes. The renewal of sources of motivation requires an analysis of the changes currently affecting the world of work and their consequences. Purpose of this study is to help people who manage human resources in the company to understand how to motivate, guide, arouse, support employees with disabilities and build appropriate motivational strategies. Results are deliberated and conclusion & recommendation for further research are formulated.